Between East and West : from singularity to community - Irigaray, Luce (European perspectives., 2002)
With this book we see a philosopher well steeped in the Western tradition thinking through ancient Eastern disciplines, meditating on what it means to learn to breathe, and urging us all at the dawn of a new century to rediscover indigenous Asian cultures. Yogic tradition, according to Irigaray, can provide an invaluable means for restoring the vital link between the present and eternity -- and for re-envisioning the patriarchal traditions of the West. Western, logocentric rationality tends to abstract the teachings of yoga from its everyday practice -- most importantly, from the.